Restrictive rental policies and a tough trade off: Lower rents vs. less construction in Geneva - Kristyna Ters; Konstantin Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
We study how rent control and housing rationing shape housing investment and market tightness in Geneva using a VAR on annual data (1994-2022) with generalized impulse responses and Granger causality. We find that housing rationing functions as abinding quantity restriction as it precedes a contraction in new institutional construction and Granger-causes lower vacancy rates. This increased scarcity is an effect amplified by persistent positive net migration. At the same time, housing rationing redirects capital toward the intensive margin as both institutional and private investors shift to stock-preserving renovations. Primarily operating through the price channel, rent control induces a transitory, statistically significant rise in private renovation investments and compliance-salient upgrades, rather than sustained new-build activity. Across both instruments, the dominant margin of adjustment is short-run renovation by private owners and institutions, not additions to stock. The policy implication is clear: without complementary, density-enabling approvals and a reduction in rent control, government regulation will continue to reallocate investment from new construction to renovations. This will tighten utilization and increase scarcity in an already demand-pressured market.
Keywords: C32; O18; R31; 330; rent control; housing rationing; real estate finance; construction investments